-3(x-3)-4(x+4)=

Simple and best practice solution for -3(x-3)-4(x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-3)-4(x+4)= equation:


Simplifying
-3(x + -3) + -4(x + 4) = 0

Reorder the terms:
-3(-3 + x) + -4(x + 4) = 0
(-3 * -3 + x * -3) + -4(x + 4) = 0
(9 + -3x) + -4(x + 4) = 0

Reorder the terms:
9 + -3x + -4(4 + x) = 0
9 + -3x + (4 * -4 + x * -4) = 0
9 + -3x + (-16 + -4x) = 0

Reorder the terms:
9 + -16 + -3x + -4x = 0

Combine like terms: 9 + -16 = -7
-7 + -3x + -4x = 0

Combine like terms: -3x + -4x = -7x
-7 + -7x = 0

Solving
-7 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -7x = 0 + 7

Combine like terms: -7 + 7 = 0
0 + -7x = 0 + 7
-7x = 0 + 7

Combine like terms: 0 + 7 = 7
-7x = 7

Divide each side by '-7'.
x = -1

Simplifying
x = -1

See similar equations:

| y=-5x^2+70x | | -w+83=207 | | 245-w=117 | | y=-5x+70x | | 4m-2m+4=-1+13 | | 4(x+4)=(4x+16) | | 5f+20= | | 6-2(x+1)+3x= | | 0.2x+3.7x+4.2x+13=2x+20 | | -4/3u=16 | | -6/7y=42 | | (3x-4)+7=23 | | -16t^2+54t+7=0 | | 24=-12u | | 2/5x-17=-11 | | 10y+5x-5y-2x+7= | | 4b^7-4b^6-24b^5= | | lx-2l+5=3 | | u/6.25=5 | | -2y+3=4y+3 | | 72.9x+40=324x-11 | | 6u+8v-7+6u-4v+8w= | | 6.2x+11=324 | | h+55+1.93=98.70 | | 400=y*(30+y) | | 7(10+7x)=7(4x+3) | | xy+3y=8x-20 | | 2x=10-3y | | 8v^2+16v-64=0 | | 23x+12=21x+34 | | (-0.4-2)+1.3= | | x/6=7.68 |

Equations solver categories